Principles of anatomy and physiology - Tortora, Gerard J.; Tortora, Gerard J.; Derrickson, Bryan (New Jersey, John Wiley & Sons, 2006)
An older edition but still comparable to the 13th Edition being used now. The 13th edition was the book i needed for my A&P I class and i was able to use the e-book that came with my Wiley Plus code and use this book as an additional reference and most things were explained better in this book. Nursing Student.
Appendix A-E, 1-15p.; Glossary G1-G37p.; Index I1-I-32p.
Keywords: Anatomy; Human anatomy; Human physiology; Biology